Prevalence of hypothyroidism in subfertile women in a tertiary care centre in North India - Singh, Kalpana; Kumari, Rekha; Kumar, Uday (International Journal of Research in Medical Sciences, 2017)
Background: Thyroid hormones are essential for normal growth, sexual development and reproductive function. The prevalence of hypothyroidism varies between 2-4% in women of reproductive age group. It can affect the fertility in various ways like sex hormone imbalance, anovulatory cycles, luteal phase defects, and hyperprolactinemia. Objectives: To study the prevalence of hypothyroidism in subfertile patients. Methods: A total of 454 subfertile women visiting the Reproductive Biology department for subfertility were investigated for thyroid stimulating hormone (TSH) and prolactin (PRL). Hypothyroidism was considered at TSH levels of >4.5 μIU/ml and hyperprolactinemia at PRL levels of >25 ng/ml. Results: Of 454 subfertile women 24% were hypothyroid (TSH >4.5 μIU/ml) and 12.8% patients had hyperprolactinemia. Conclusions: TSH and PRL should be measured in all cases desirous of issue before proceeding for more costly tests or invasive procedures.